THE BASIC LAWS OF GEOPOLITICS IN THE CONDITIONS OF WORLD SPACE ORGANIZATION - Степаненко, Анатолій (Human Geography Journal, 1970)
The basic laws of geopolitics in the conditions of globalization processes are enlightened: planetary dualism, which acquires the signs of global tetracracy of the elements: tellurocracy, thalassocracy, aerocracy and cosmocracy; strengthening of the factor of space in human history; synthesis of land and sea; global expansion; global hegemony. Their specificities and meaning in geopolitics of world are revealed. The changes of configuration of geopolitical space, new geopolitical challenges and priorities in the conditions of globalization are enlightened.